The effect of vitamin D supplementation on antibiotic use: a meta-analysis based on randomized controlled trials - Wang, Mian; Wu, Yixuan; Xiang, Zhiyi; Zhang, Yueming; Huang, Tingyi; Chen, Bangsheng (Frontiers in Nutrition, 2024)
Objective: This meta-analysis explores the impact of vitamin D supplementation on antibiotic utilization. Methods: We systematically searched for relevant randomized controlled trials (RCTs) in PubMed, Web of Science, EMBASE, and Science Direct from inception to April 2024. These trials compared antibiotic use rates between groups receiving vitamin D supplements and placebo. Results: We included seven RCTs involving 35,160 participants. There was no significant difference in antibiotic use between the two groups in the general population (Odds Ratio [OR] = 0.98, p = 0.232), including elderly participants (OR = 0.98, p = 0.295). However, antibiotic use was lower in the intervention group compared to the placebo group among participants under 70 years of age (OR = 0.95, p = 0.015), those with relative vitamin D deficiency (25(OH)D <75 nmol/L, OR = 0.95, p = 0.024; 25(OH)D <50 nmol/L, OR = 0.96, p = 0.026), and those with respiratory tract infections (RTIs) (OR = 0.51, 95% CI: 0.24-1.08, p = 0.080), although these differences were not statistically significant for RTIs. Conclusion: Vitamin D supplementation does not affect antibiotic use in the general population. However, it does reduce antibiotic utilization in individuals with RTIs, relative vitamin D deficiency, or aged below 70 years.